ZnAs₂ electrical conductivity at cyclic pressure treatment in the 22−50 GPa range - Babushkin, A.N.; Perevalova, S.V.; Mollaev, A.Y.; Saypulaeva, L.A.; Marenkin, S.F.; Morozova, V.A. (Физика и техника высоких давлений, 2007)
The aim of the work is to investigate ZnAs₂ electrical conductivity at cyclic pressure treatment in the range of 20−50 GPa, to determine concrete values of pressure, at which the changes take place in this material, and to reveal peculiarities of behaviour at pressures up to 50 GPa.